Determination of Hydroquinone and Retinoic Acid in Whitening Creams in Ujung Berung Market Bandung, Using UV-Visible Spectrophotometry - Shalihat, Ayu; Putri, Syakira Dwi; Fadhilah, Khusnul (Universitas Padjadjaran (Unpad), 2024)
Whitening creams are cosmetic products applied to the skin to brighten or alter skin tone. The use of retinoic acid and hydroquinone without medical supervision is prohibited under Indonesian Food an Drug Authority (BPOM) regulations, as these are classified as prescription drugs that may cause harmful side effects with long-term use, such as skin irritation, dryness, burning sensation, and teratogenic effects. Unfortunately, these substances are still misused in some facial whitening products. This study aimed to identify the presence and determine the concentration of retinoic acid and hydroquinone in facial whitening creams sold in Ujung Berung Market, Bandung City. Samples were selected using purposive sampling with the criteria of being low-cost and without a registration number. A total of four cream samples were analyzed qualitatively using Thin Layer Chromatography (TLC) with a mobile phase of acetone:n-hexane (4:6), and quantitatively using UV-Visible spectrophotometry. Absorbance measurements for retinoic acid and hydroquinone were performed at wavelengths of 324 nm and 300 nm, respectively. TLC results showed that two samples, B and D, tested positive for retinoic acid with Rf values of 0.52 and 0.55, respectively, exhibited dark blue spots similar to the standard. The result of hydroquinone analysis using TLC was unidentified. Quantitative analysis revealed that sample B contained the highest retinoic acid concentration (0.077% w/w), while sample A had the highest hydroquinone concentration (0.604% w/w). These findings suggest that some facial whitening creams sold in Ujung Berung Market still contain unauthorized levels of retinoic acid and hydroquinone, highlighting the need for stricter regulation and public awareness.